Small is beautiful and important: economies and firms trading in digital services - Kerner, Riina; Kitsing, Meelis (Journal of Business Economics and Management, 2023)
Although many firms operate on global digital platforms, small countries and firms also play an essential role at the national level, especially during crises and the slowdown in globalization. This research investigates trade patterns in digital services at the country and firm level and identifies challenges in this area in providing new information and tools to startup mentors and policymakers, who need more evidence for national authorities to develop mentorship and digital programmes. The study also contributes to transaction cost theory, explaining how it is possible to reduce transaction costs. The methodology involves using quantitative and experimental methods, logistic regression for firms and correspondence analysis for countries. The WTO dataset was used to visualise trade in services data and to interpret clusters of digitalised countries. Interestingly, Estonia stands apart from other post-socialist countries in terms of digital services exports, being among smaller countries and hosting the highest concentration of startups per capita. The firmlevel analysis revealed that firms trading in digital services differ from others – being smaller, more focused on exports and more often controlled by non-residents. The study encourages investments in small countries and small firms that trade successfully in digital services.